Some New De Morgan Picture Operator Triples in Picture Fuzzy Logic - Cong, Cuong Bui; Ngan, Roan Thi; Long, Le Ba (Journal of Computer Science and Cybernetics, 2018)
A new concept of picture fuzzy sets (PFS) were introduced in 2013, which are direct extensions of the fuzzy sets and the intuitonistic fuzzy sets. Then some operations on PFS with some properties are considered in [ 9,10 ]. Some basic operators of fuzzy logic as negation, tnorms , t-conorms for picture fuzzy sets firstly are defined and studied in [13,14]. This paper is devoted to some classes of representable picture fuzzy t-norms and representable picture fuzzy t-conorms on PFS and a basic algebra structure of Picture Fuzzy Logic – De Morgan triples of picture operators.